DATA SCIENCE AS THE EPISTEMIC INFRASTRUCTURE OF THE STATE: : DIGITAL GOVERNANCE AND REPUBLICAN VALUES IN PUBLIC POLICIES (Interdisciplinary Studies Journal, 2026)
This essay analyzes the integration of Data Science, analytical infrastructure, and Digital Governance in Public Administration, emphasizing the precedence of republican values and democratic legitimacy in evidence-informed decision-making. It proposes understanding Data Science as the State’s epistemic infrastructure, responsible for structuring the production of evidence and expanding the analytical capacity of governmental action. Within this framework, public values, institutional governance, and technical infrastructure constitute interdependent dimensions that condition the legitimacy of data-oriented decisions. The study examines risks associated with algorithmic rationality, including the autonomization of technique, decision opacity, and the reproduction of inequalities, and discusses institutional mediation mechanisms based on Digital Governance, human oversight, and contestability. Documented cases and an analytical exercise illustrate how subordinating technical systems to republican values can guide legitimate public decisions. By articulating conceptual foundations, analytical architecture, and institutional implications, the essay contributes to debates on digital Public Policies and to the understanding of state capacities in contexts of algorithmic governance.
Keywords: Artificial Intelligence; Data Science; Digital Governance; Evidence-Informed Public Policies